CHARACTERISTICS OF SLEEP DISORDERS IN PLAQUE PSORIASIS PATIENTS TREATED WITH BIOLOGICS AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of sleep disorders and related factors in patients with plaque psoriasis undergoing maintenance treatment with biologics at Bach Mai Hospital.Methods: A cross-sectional descriptive study was conducted on 62 patients with plaque psoriasis receiving outpatient treatment with biologics (including Secukinumab, Ustekinumab, and Guselkumab) at Bach Mai Hospital from January 2025 to November 2025. Sleep quality was assessed using the PSQI, disease severity was evaluated using the PASI, and itch intensity was measured using the PNRS.Results: The mean age of the study group was 46.5 ± 12.4 years, with 82.3% of patients treated with Secukinumab. The mean PASI score was low (2.8 ± 3.1). The mean PSQI score was 5.8 ± 3.4. The prevalence of sleep disorders (PSQI > 5) was 43.5%. The most common disturbances were short actual sleep duration (5.9 ± 1.4 hours/night) and difficulty falling asleep (sleep latency). There was a moderate positive correlation between itch score (PNRS) and PSQI score (r = 0.45; p = 0.001). No statistically significant correlation was found between the PASI score and sleep quality (p > 0.05).Conclusion: Although biologics provide effective control of skin lesions, a significant proportion of patients still experience sleep disorders. Itch severity is the primary factor affecting sleep quality rather than the degree of skin clearance.
Keywords: Psoriasis, biologics, sleep disorders, PSQI, PASI, PNRS.